WATER RESOURCES QUALITY ASSESSMENT USING BENTHIC MACROFAUNA BY COMMUNITY PARTICIPATORY: A CASE STUDY OF SAKLEEWITTHAYA SCHOOL, SENA DISTRICT, AYUTTHAYA PROVINCE - To-orn, Natthakitt (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The study of benthic macrofauna in the Sakleewitthaya School, Sam Tum Subdistrict, Sena District, Ayutthaya Province, with community participation, aims to adapt the BMWPthai score (Biological Monitoring Working Party) and ASTPthai (Average score Per Taxa) biological indices to assess water quality. Samples of benthic fauna were collected from four stations in August 2022. The study revealed 17 species belonging to 16 families of benthic fauna from six major groups, including roundworms (nematodes), aquatic oligochaetes, gastropods, bivalves, crustaceans, and aquatic insects. Aquatic insects were the most diverse species, followed by gastropods and crustaceans, respectively. The red-rimmed melania, Melanoides tuberculate (family Thaiaridae), the Asian glass shrimp, Macrobrachium lanchesteri (family Palaemonidae), and river snails, Filopaludina martensi (family Viviparidae), were abundant. The BMWPthai score and ASTPthai revealed that the overall water quality was categorized as "satisfactory" or "moderate" in surface water quality standards class 3, with ASTPTthai scores ranging from 4.30 to 5.88. This research was conducted collaboratively with the community, aiming to enable the community to use the benthic fauna-based water quality monitoring method to track changes in water quality within their community effectively. It a guideline for efficient and sustainable cooperation in improving water quality at local water sources.